Nutrient Digestibility and Apparent Bioavailability of Minerals in Beef Cattle Fed with Different Levels of Concentrate and Oil-palm Fronds - Warly, Lili; Suyitman; Evitayani; Fariani, Armina (Pakistan Journal of Nutrition, 2017)
Objective: This experiment was carried out to determine the effects of various levels of concentrate and oil-palm fronds (OPF) on nutrient digestibility and apparent mineral bioavailability in beef cattle. Materials and Methods: Fifteen Simmental cattle were allocated to three experimental diets in a random block design. Dietary treatment 1 (diet 1) contained 40% concentrate and 60% OPF, dietary treatment 2 (diet 2) contained 50% concentrate and 50% OPF and dietary treatment 3 (diet 3) contained 60% concentrate and 40% OPF. The concentrate consisted of rice bran, tofu waste and ex-decanter solid waste from palm-oil processing, no mineral supplement was given in this study. Results: The results of the study showed that the digestibility of dry matter, crude fiber, crude protein, Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and cellulose were significantly higher (p<0.01) in cattle given 60% concentrate and 40% OPF (diet 3). The apparent bioavailability of both macro and micro-minerals in diet 3 was significantly higher (p<0.01) than in the other diets. The apparent bioavailability of calcium (Ca), magnesium (Mg), phosphorus (P) and sulfur (S) in diet 3 were 46.5, 48.9, 53.7 and 52.1%, respectively, while the apparent bioavailability of iron (Fe), manganese (Mn), cobalt (Co) and zinc (Zn) were 38.9, 30.7, 36.6 and 41.5%, respectively. These results indicated that increasing the amount of OPF up to 60% as a main source of forage in the rations of beef cattle reduced the nutrient digestibility and apparent bioavailability of minerals. The diet containing 60% OPF resulted in a greater deficiency of minerals, whereas increasing the level of concentrate from 40-60% significantly reduced the deficiency of minerals (p<0.01). Furthermore, the apparent bioavailability of minerals was low overall and all three experimental diets were deficient in minerals, showing that supplementation of certain minerals is needed to support optimum production of beef cattle. Conclusion: Based on these results, it could be concluded that feeding beef cattle with 60% concentrate and 40% OPF results in higher digestibility of nutrients and improved bioavailability of minerals and reduces deficiency of minerals.